Strategi Tahfidzul Qur'an di Dayah Ulumul Qur'an Kecamatan Seunagan Kabupaten Nagan Raya - Safariah Safariah; Masykur Masykur (Program Studi PGMI STAI Daruttaqwa Gresik, 2022)
The purpose of this study was to determine the planning, implementation, and evaluation at Dayah Ulumul Qur'an, Seunagan District, Nagan Raya Regency. This research was conducted with a field study using a qualitative descriptive method. Data collection techniques were carried out through interviews, observation, and documentation. The results showed that the planning or design of ta?f?z al-Qur'an at MUQ Nagan Raya was carried out by each teacher when he wanted to teach. Planning in MUQ Nagan Raya tahfidz learning includes; an annual programa, semester program, and daily lesson plans. Meanwhile, daily learning planning is carried out by each ta?f?z teacher individually, with flexibility according to abilities and conditions in the field. Implementation of Tahfidz Al-Qur'an at MUQ Nagan Raya Regency in a day there are three halaqah Al-Qur'an, the first two halaqah are at 04.45 WIB until 8.30 WIB and one halaqah is available at 12.30 to 13.30, and continued again at 18.45 to 20.30 WIB. Evaluation of ta?f?z at MUQ Nagan Raya Regency is carried out in the form of oral, written, or deed. Musyrif who plays a very important role in daily evaluation, both in terms of morals and daily targets.